Peran Orang Tua dalam Menumbuhkan Kebiasaan Literasi pada Siswa Sekolah Dasar - Amniar Ati (Jurnal Pendidikan Dasar, 2026)
Literacy habits are very important to instill in children from an early age, because through literacy children can develop reading and writing skills, as well as the ability to understand information effectively. In addition, literacy helps improve critical thinking, creativity, and communication skills, enabling children to be better prepared to face both the learning process and everyday life. This study aims to examine the role of parents in fostering literacy habits among elementary school students at SD Negeri 40 Buton. This research uses a quantitative approach with a descriptive research design. The population in this study consists of all parents of students in grades III, IV, and V, totaling 48 individuals, with the sampling technique using total sampling. Data collection techniques were carried out through observation and questionnaires. Data analysis used descriptive analysis with percentages. The results of the study indicate that the role of parents in fostering students’ literacy habits is still relatively low. This can be seen from indicators such as the literacy environment at home, parental involvement in children’s literacy activities, and the habituation of shared reading activities, all of which have percentages below 40%. Most parents have not provided adequate reading materials, have not actively accompanied and motivated their children in reading activities, and have not established regular shared reading habits at home.